Stages of individuals and the composition of states - Husband, M (De Gruyter, 2012)
Whether a stative predicate licenses an existential interpretation of its subject (EIS) depends in part on the type of object it has. While previous theories have related this to the object's ability to function as a topic, this paper presents evidence that the quantized/homogeneous distinction between objects better captures EIS and proposes an event composition analysis of EIS for (transitive) stative predicates. This analysis points to the aspectual nature of EIS and also illuminates other aspectual behaviors of stage-level/individual-level states.